H₂O₂로 유발된 Neuro2A 신경세포고사에 대한 줄풀의 억제 효과 - 박원형(Won Hyung Park); 차윤엽(Yun Yeop Cha) (동의생리병리학회지, 2005)
The purpose of this study was to examine the inhibition effect of Zizania latifolia that has been used heart disease, Diabetes Mellitus and Skin disease for a long time on apoptosis induced by H2O2 in Neuro2A cell. Neuro2A cells were cultivated in RPMI(GibcoBRL) with 5% FBS and treated with H2O2 and Zizania latifolia. We measured the cell viability and analyzed DNA fragmentation. Activity of PARP, Cytochrome C, caspase-9, caspase-3, p53, p21, Bax and Bcl-2 in the cell was examined by using western blot. The cell viability in Zizania latifolia treatment (60ug/ml<) decreased significantly compared with that of none treatment. (P<0.001) Zizania latifolia increased cell viability about twice as much as that being injury by H2O2. (Zizania Latifolia 20ug/ml, H2O2 200uM, P<0.001) DNA fragmentation developed by H2O2, but was not developed in Zizania latifolia treatment. PARP, Cytochrome C, caspase-9 and caspase-3 activated all by H2O2 but were not activated in Zizania latifolia treatment.. P53, P21 and Bax activated by H2O2, and Bcl-2 got into inactivation. But the opposite results appeared in Zizania latifolia treatment. In conclusion, these results suggest that Zizania latifolia inhibit the development of DNA fragmentation and apoptosis by H2O2 and the antioxidant action of Zizania latifolia is effective. More researches about effect of Zizania latifolia are considered to need. KCI Citation Count: 3